2011
DOI: 10.1371/journal.pntd.0000934
|View full text |Cite
|
Sign up to set email alerts
|

DC-SIGN (CD209) Promoter −336 A/G Polymorphism Is Associated with Dengue Hemorrhagic Fever and Correlated to DC-SIGN Expression and Immune Augmentation

Abstract: BackgroundThe C-type lectin DC-SIGN (CD209) is known to be the major dengue receptor on human dendritic cells, and a single nucleotide polymorphism (SNP) in the promoter region of CD209 (−336 A/G; rs4804803) is susceptible to many infectious diseases. We reason that variations in the DC-SIGN gene might have a broad influence on viral replication and host immune responses.Methods and FindingsWe studied whether the rs4804803 SNP was associated with a susceptibility to dengue fever (DF) and/or dengue hemorrhagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 40 publications
4
62
1
Order By: Relevance
“…Additionally, Sakuntabhai et al (2005) found initial evidence for the association of this SNP with the pathogenesis of dengue virus infection. These authors found that allele -336G was associated with disease severity, a finding corroborated by a more recent case-control study, in which Wang et al (2011) demonstrated that the GG and AG genotypes were associated with increased susceptibility to dengue hemorrhagic fever, the most severe form of the disease.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Additionally, Sakuntabhai et al (2005) found initial evidence for the association of this SNP with the pathogenesis of dengue virus infection. These authors found that allele -336G was associated with disease severity, a finding corroborated by a more recent case-control study, in which Wang et al (2011) demonstrated that the GG and AG genotypes were associated with increased susceptibility to dengue hemorrhagic fever, the most severe form of the disease.…”
Section: Introductionsupporting
confidence: 52%
“…In this study, we described the frequency of CD209 SNP -336A/G in a population from Piauí State, located in northeastern Brazil. This SNP has been associated with infectious diseases of different etiologies, notably those of viral origin (Kashima et al, 2009;Chan et al, 2010;Ryan et al, 2010;Wang et al, 2011;Barkhash et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is evidence for several candidate host receptors, for example mannose binding protein, heparan sulphate, chondroitin sulphate and DC-SIGN. [127][128][129] The factors that determine the number of cells infected at specific sites may also influence the level of immune activation, and thus have a role in determining the disease phenotype. 111,125 The time between the bite of an infected mosquito and the onset of clinical symptoms is believed to be 3-5 days 130,131 Whether infected individuals in this presyndromic phase are capable of transmitting virus to a biting mosquito is unknown.…”
Section: Cellular and Tissue Targets Of Den Virus Infectionmentioning
confidence: 99%
“…IP-10 is an antigen-presenting cell chemokine induced by IFN-␥ that was also shown to competitively inhibit DENV attachment to new cells, resulting in a decreased DENV titer (40). Similarly, an approximately 2-fold decrease in the average IP-10 concentration was demonstrated to increase the DENV titer in monocyte-derived dendritic cells (41). As potential internal controls for normalization, we also measured the transcript levels of the genes for GAPDH and L-32.…”
Section: Discussionmentioning
confidence: 99%